International Relations Theory : the game theoretic approach - Kydd, Andrew H., 1963- (New York : Cambridge University Press, 2015)
"Written for advanced undergraduate and graduate students, this is the first textbook on international relations theory to take a specifically game theoretic approach to the subject, and provide the material needed for students to understand the subject thoroughly, from its basic foundations to more complex models. International relations theory is presented and analysed using simple games, which allow students to grasp the concepts and mechanisms involved with the rationalist approach without the distraction of complicated math. Chapter exercises reinforce key concepts and guide students to extend the models discussed. Drawing examples from international security, international political economy and environmental negotiations, this introductory textbook examines a broad array of topics in international relations courses, including state preferences, normal form games, bargaining, uncertainty and communication, multilateral cooperation and the impact of domestic politics"--
Machine generated contents note: 1. Introduction; 2. What states want; 3. Varieties of strategic settings; 4. Bargaining; 5. Power change and war; 6. Private information and war; 7. Arms competition and war; 8. Cooperation theory; 9. Diplomacy and signaling; 10. Multilateral cooperation; 11. Domestic politics and international relations.
(3SjO GdJhfSj (B/ (3cJH cdjI GdGbJUGO hGdGOGQI(B.s
Includes bibliographical references and index.
Keywords: International relations; Game theory; POLITICAL SCIENCE / International Relations / General